2022
DOI: 10.3389/fneur.2022.1014501
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and predictive models of poor prognosis and delayed cerebral ischemia in aneurysmal subarachnoid hemorrhage complicated with hydrocephalus

Abstract: ObjectiveTo evaluate the correlation of serum biological markers and related scales to the occurrence of delayed cerebral ischemia and clinical prognosis in patients with aneurysmal subarachnoid hemorrhage (aSAH) complicated with acute hydrocephalus before admission.MethodsThe clinical data of 227 patients with pre-admission aSAH complicated with acute hydrocephalus admitted to Henan Provincial People's Hospital from April 2017 to December 2020 were retrospectively analyzed. Patients were grouped according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
(50 reference statements)
2
8
0
Order By: Relevance
“…In the present study, the demographic and clinical manifestations were similar to those in previous studies [ 31 ]. Age was significantly associated with neurological deterioration among patients with aSAH.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, the demographic and clinical manifestations were similar to those in previous studies [ 31 ]. Age was significantly associated with neurological deterioration among patients with aSAH.…”
Section: Discussionsupporting
confidence: 89%
“…The mean TC and LDL in the patients were 162.3 mg/dl (95% CI: 139.2-185.3) and 77.59 mg/ dl (95% CI: 64.24-90.93), respectively, without differences from controls. The median GCS (interquartile range) at the time of presentation was 13 (9-15), while the median Hunt-Hess scale was 2 (2-3), the median Fisher grade was 4 (3-4), and the median WFNS was 2 (1)(2)(3)(4). The GOS at 6 months was 5 (3)(4)(5).…”
Section: Resultsmentioning
confidence: 99%
“…Aneurysmal subarachnoid hemorrhage (aSAH) accounts for 5% of all types of stroke, has a mortality of 35%, and most survivors have long-term disabilities or cognitive dysfuntion. [1][2][3] The mechanisms of secondary brain injury after aSAH are multifactorial and start immediately after bleeding. Recent evidence shows that inflammation mediates many of the vascular and neural changes observed in the acute phase after aSAH (0-24 hours after hemorrhage).…”
Section: Introductionmentioning
confidence: 99%
“…The Hunt-Hess grading system, a simple and effective clinical grading scale for SAH, was designed to standardize the clinical assessment of SAH and facilitate patient management ( 24 ). Multiple studies have shown that the prognosis of patients with aSAH was significantly correlated with the Hunt-Hess grade ( 25 , 26 ). In addition, our results showed that the Hunt-Hess grade was a solid predictor of poor outcomes in patients with poor-grade aSAH who underwent microsurgical clipping.…”
Section: Discussionmentioning
confidence: 99%